Pola produksi dan nutrisi rumput Kume (Shorgum plumosum var. Timorense) pada lingkungan alamiahnya - Yohana Kamlasi; Marthen L. Mullik; Twen O. Dami Dato (Faculty of Animal Science, Universitas Brawijaya, 2014)
The purpose of the study was to know the production system and nutrition content of Kume grass (Shorgum plumosum var. Timorense). The study used experimental method. The data were analyzed descriptively to know the production system and nutrition content of Kume grass. Two variables namely independent variables (cutting age) and dependent variables (nutritive values, plant height, dry matter production, organic matter and crude protein) were analysed statistically using correlation. The growth pattern of Kume grass from 14 to 112 days was polinomial. The increase of cutting age was followed by the increase of dry matter, organic matter, crude fiber and the decrease of crude protein. The crude fiber also increased together with the cutting age. Keywords:growth, production, nutrition, Kume grass